2011
DOI: 10.1097/olq.0b013e31820369dd
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Not HIV Testing, Testing Intentions, and Potential Use of an Over-the-Counter Rapid HIV Test in an Internet Sample of Men Who Have Sex With Men Who Have Never Tested for HIV

Abstract: Among NTMSM who use the internet, main reasons for not testing for HIV vary considerably by age, race/ethnicity, UAI, and use of the internet for HIV information. To facilitate HIV testing of NTMSM, programs should expand interventions and services tailored to address this variation. If approved, OTCRT might be used by many NTMSM who might not otherwise test for HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
95
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 63 publications
10
95
4
Order By: Relevance
“…Overall, these results highlight the importance of primary HIV prevention that emphasizes both the HIV risk inherent even in infrequent or rare risk behavior, as well as the importance of frequent, routine HIV testing, regardless of perceived risk. [40][41][42] Results from this study also show that unemployed MSM were significantly less likely to be recently tested for HIV, even after controlling for whether they engaged in risky sexual behavior. Importantly, income was not associated with recent HIV testing, and the ''employed'' group included individuals who were full-time students, suggesting that the observed association is not being driven by access to financial resources alone.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Overall, these results highlight the importance of primary HIV prevention that emphasizes both the HIV risk inherent even in infrequent or rare risk behavior, as well as the importance of frequent, routine HIV testing, regardless of perceived risk. [40][41][42] Results from this study also show that unemployed MSM were significantly less likely to be recently tested for HIV, even after controlling for whether they engaged in risky sexual behavior. Importantly, income was not associated with recent HIV testing, and the ''employed'' group included individuals who were full-time students, suggesting that the observed association is not being driven by access to financial resources alone.…”
Section: Discussionmentioning
confidence: 57%
“…[37][38][39] However, the relationship between HIV testing and risk behavior among MSM gives reason for concern. On the one hand, research suggests that MSM who do not test frequently believe that their HIV risk is ''low,'' [40][41][42] despite the CDC characterization of MSM as ''high risk'' group. 35 In a study providing HIV testing in bathhouses, Mayer reported that two-thirds of the MSM who engaged in UAI in the 2 months prior to HIV testing considered their HIV risk to be low, 43 suggesting that some MSM inaccurately assess the risk associated with their behavior.…”
mentioning
confidence: 99%
“…One dimension could certainly relate to lack of faith in the confidentiality of testing in routine services, and consequent fear of discrimination. Discrimination and stigma are well known barriers to testing 1,8,23,25,26,27,28,29 . Respondents also reported low levels of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Lan Zhang et al reported that no perceived risk of HIV infection and not knowing where to get a test were among the top five reasons for not taking an HIV test [10]. Perception of a low risk of HIV infection was mentioned as being among the major barriers to testing in another study from China [11], and a study in six US cities [12].…”
Section: Discussionmentioning
confidence: 99%